Educação financeira : análise de uma proposta desenvolvida no 7º ano no ensino fundamental - Scolari, Lidinara Castelli (2014)
The use of knowledge related to financial education has been presented as a differentiated strategy for taking conscious and ecologically correct financial decision. This fact indicates the necessity and the importance of including in basic education s curriculum the financial education content. With this perception, we developed a survey involving a didactic-pedagogical proposal, in a class of seventh grade of elementary school, in a municipal school of Getúlio Vargas/RS, a city located in the northern of Rio Grande do Sul state. The guiding research question is expressed as follows: in what proportion interactive processes interfere with or potentiate the appropriation of meanings of content related to financial education? Thus, the objective of this research is to analyze if the interactions produced in the development of the didactic-pedagogic allow the appropriation of meanings of contents linked to financial education in order to raising awareness on the part of students about its importance and necessity for taking conscious financial decisions. The research methodology is a qualitative approach, and its objects of analysis was composed of audio recordings of classes, material produced by students, teaching/lessons plans and memories of the teacher/researcher. The analytical study of this research was developed according the theory of cultural-historical theory, especially on social interactions and attribution of meaning in the concept formation process, highlighting the studies of Leontiev (1978), Vygotsky (1998) and Vygotsky (1998). It was found that the development of didactic-pedagogic proposal enabled social interactions in the classroom, that have contributed significantly and have worsened the attribution of meaning to the content studied, and the teacher / researcher can reflect on their practice for her qualification. It is concluded that the pedagogical proposals that prioritize social interaction for the attribution of meaning qualify the teaching-learning process and provide the cognitive evolution of subjects involved. Generally, provide to teachers reflecting on their practice, with demands for continuous training to the achievement of their actions and professional development